Moving towards critical thinking in classroom / Norlaila Abdullah - Abdullah, Norlaila (2009)
Problems are multitudinous; they can be economic, political conflicts, high failure rate among students and many more. We can solve these through critical thinking, a self-guided, self disciplined dispositions aims to take the reasoning to a higher level naturally. Surveys indicate that schools and universities are not teaching the skills and dispositions of the critical minds and, thus, students' intellects are not cultivated. The need for designing a typical class day is imperative so that students could design and be actively and thoughtfully involved in the thinking process. To inculcate students' critical thinking in strategic management class, an innovative and teaching-learning approach has been crafted. The students, working in groups, were required to think of a product of their choice to innovate. The end products were used as replica in learning the concepts and principles in class and forcing the students to reason out clearly. Results indicate that students' improvement in application, analysis and evaluation were evident. Relatively, the students were able to think deeply for themselves (85%), motivate to ask questions at the rate of agree and strongly agree of 75% and 25% respectively, and think within the logic of strategic management (95%) and complexities (90%). Simultaneously, students' final examination average marks were satisfactory at 65%. However, fostering critical thinking in classroom is the least effective in the absence of explicated replica as a teaching-learning tool.